THE NATIONAL CULTURE DEVELOPMENT UNDER CONDITIONS OF GLOBALIZATION - Шебітченко, А. П.; Блоха, Я. Є. (Proceedings of the National Aviation University Series Philosophy Cultural, 2015)
A short analysis of different points of view concerning the problem of national culture functioning under conditions of globalization and the ways of resolving conflicts in this process is made in the article.